Lateral Behaviors of Nested Tube Systems Under Quasi-Static Condition - TrongNhan, Tran; Estrada Barbosa, Quirino; Arameh, Eyvazian; DucHieu, Le; NhatTan, Nguyen; HuuSon, Le (2020)
A study is made to investigate the compression behavior of different nested tube systems made of mild steel under lateral compression. The nested tube systems including stacked groups of circular, rectangular and square tubes are built for application in narrow compressive zones. The deformation mode of these systems is observed and their lateral compression behavior are identified. The desirable stepwise energy absorption is obtained by designing the nested tube system. The load response revealed that there is no appearance of the peak compressive load in the case of a circular-circular tube (CCT) system, while a circular-rectangular tube (CRT) system offers bigger peak compressive load compared with that of a circular-square tube (CST). The energy absorptions of CCT and CRT systems are smallest and greatest, respectively. This study also estimates the energy absorption capacity of these system. By implementing the “plastic hinge line” concept of the modified simplified super folding element (MSSFE) theory and superposition principle, the analytical models predicting compressive load of the nested tube systems are introduced. The analytical investigations are compared with the data obtained from tests on these systems. Excellent correlation is observed between the theoretical and experimental data.